PENERAPAN SISTEM MANAJEMEN KESELAMATAN DAN KESEHATAN KERJA DI RSUD DEMANG SEPULAU RAYA KABUPATEN LAMPUNG TENGAH TAHUN 2024 - Eka Wulandari, Windi; Hasan, Amrul; Sutrio, Sutrio (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
Hospital is a health service institution that organizes comprehensive individual health services that provide inpatient, outpatient, and emergency services (President of the Republic of Indonesia, 2009). In addition to being required to be able to provide quality services and treatment, Hospitals are also required to implement and develop Occupational Health and Safety (K3) programs in Hospitals (SMK3) as stated in the Hospital Service Standards book and contained in the Hospital accreditation instrument.This study aims to determine the implementation of the Occupational Health and Safety Management System at the Demang Sepulau Raya Hospital, Central Lampung. The study was conducted using a qualitative descriptive approach. The number of informants was 5 people with the variables studied being: 1 Head of Hospital, 1 Head of General Personnel and Administration, 1 Head of Education and Training Section, 1 Secretary of the K3RS Committee, 1 Head of Sanitation Installation. Data collection was carried out by interview and observation. The results of the study were compared with PP No. 50 of 2012 and the data was presented in a table with a narrative.The results of the study show that Demang Sepulau Raya Regional Hospital has implemented the SMK3 policy in accordance with Permenkes No. 50 of 2012 by having a commitment to implementing K3, providing K3 facilities and infrastructure, and having professional human resources in the field of K3. However, some human resources do not show a commitment to the K3 that is implemented and Demang Sepulau Raya Regional Hospital only provides one other technical staff as K3 staff in the hospital, so it is better for Demang Sepulau Raya Regional Hospital to be expected to improve the implementation of recording and reporting documents from all types of K3 activities/K3 programs to become indicators for further K3 planning and implementing worker health surveillance